Micromorphological studies of the leaf epidermis of Iranian Cotoneaster Medik. (5th March 2019) - Raei Niaki, Nemat Allah; Attar, Farideh; Mirtadzadini, Mansour; Mahdigholi, Kazem; Sheidai, Masoud
Abstract : In this study, micromorphological features of the leaf epidermal cells of 17 species of Iranian Cotoneaster were determined. The studied species were compared with each other and with phylogenetic relationships established by previous studies. Three populations of C. integerrimus and C. multiflorus were studied as representatives of C . subgen. Cotoneaster and Chaenopetalum, respectively. To evaluate quantitative and qualitative characters, multiple correspondence analysis (MCA) and factor analysis of mixed data (FAMD) were performed. Finally, relationships among the taxa were illustrated by hierarchical clustering analysis. Three stomatal types were identified, i.e. anomocytic, stephanocytic and actino‐stephanocytic. The wax and cuticle density was higher in species from semi‐moist habitats than in those from dry and semi‐dry habitats. The patterns formed by the anticlinal walls of the epidermal cells were sinuous, repand and straight‐curved. Interestingly, there was a significant relationship between the length of leaves, the density of the indumentum and the pattern formed by the anticlinal cell walls. The leaves of species with large leaves also have lower hair density and more curved anticlinal cell walls. It appears probable that climatic conditions affected the evolution of leaf micro‐morphological characters during the early diversification of the genus, but that these characters have subsequently been permanently fixed by phylogenetic constraints and thus appear diagnostic for extant species.